Above+ground. - Wu, Siyi. (2011)
My Final Year Project (FYP) series of images titled ABOVE+GROUND aims to distinguish between seeing and looking, and thus provide the viewers with a new way of visually perceiving our surroundings, particularly on the publicly owned streets at night. Unabsorbed rainwater reflections on the pavements were photographed during nighttimes, capturing the two different geometric planes that include both the pavement and the aboveground electronic light-emitting structures, onto the single ground surface. By just looking at the ground-surface water that serves as the merger to combine these two different geometric planes, it would generate an innovative way to view the streets. Not only would it arouse the viewers’ curiosities to identify the reflected structures surrounding the streets, their usual impressions of the streets at night would changed, questioning their relationship between the surroundings and themselves; and the harmonious union of the pavement textures and the presence of the colourful lights would also produce a different night street beauty.